PERANAN MEDIASI DALAM REKONSILIASI PERSELISIHAN RUMAH TANGGA (Studi di PA Kota Tasikmalaya) - Rahman, Adam (Al-Ahwal: Jurnal Hukum Keluarga Islam, 2014)
Marriage is a contract handover between men and women with the purpose to satisfy each other and to form acomfort household and prosperous society. But not a few of the couples, who have tied up in domestic bonds,experience household problems. Household bond vulnerability to interference and problem that break the continuityof the household of which are caused by economic factors, unpreparedness couples to navigate the household, nomutual respect between partners who all accumulated into a dispute that could be the reason of the divorce.Disputes arising in a household often become a classic and became one of the common reasons for divorce filed alawsuit to religious courts. Whatever the reason, Islam basically wants an eternity in the household and hates adivorce. At the Religious Court of Tasikmalaya, number of divorces is still quite high with a variety of reasonsbehind it.[Perkawinan adalah akad serah terima antara laki-laki dan perempuan dengan tujuan untuk salingmemuaskan satu sama lain dan untuk membentuk sebuah bahtera rumah tangga yang sakinah sertamasyarakat yang sejahtera. Namun tidak sedikit dari pasangan suami istri yang sudah terikat dalamikatan rumah tangga, mengalami permasalahan dalam mengarungi bahtera rumah tangga. Rentannyaikatan rumah tangga terhadap gangguan dan permasalahan yang dapat menghancurkan keberlangsunganrumah tangga diantaranya disebabkan oleh faktor ekonomi, ketidaksiapan pasangan untukmengarungi rumah tangga, tidak saling menghargai antar pasangan yang kesemuanya terakumulasimenjadi sebuah perselisihan yang bisa menjadi alasan dari perceraian. Di Pengadilan Agama KotaTasikmalaya, jumlah perceraian masih cukup tinggi dengan berbagai alasan yang melatar belakanginya.]